2017
DOI: 10.30738/spirits.v5i2.1065
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Konsep Diri Dengan Kecenderungan Gaya Hidup Hedonisme Pada Mahasiswi Psikologi Ust Yogyakarta

Abstract: This study aims to determine the relationship between self-concept and lifestyle trends hedonism student of Psychology, University of SarjanawiyataTamansiswaYogyakart. The hypothesis of this study is that there are ties between the negative self-concept and lifestyle of hedonism on a college student.The subjects were female students of UST Psychology Yogyakarta, 18-22 years old, female, amounting to 87 people. Measuring instrument used was a self-concept scale and the scale of the lifestyle of hedonism. Analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
1
2
0
3
Order By: Relevance
“…Based on this, in line with the results of research by Brilliandita & Putrianti (2017), adolescents, in this case, students, who are dominant with a hedonic lifestyle, become unproductive, and in adolescent relationships, are more concerned with appearance or prestige. A hedonic lifestyle that must be supported by adequate financial capabilities will also become an even bigger problem if the achievement is carried out in all unhealthy ways, which will result in moral siltation for female students who adhere to a hedonic lifestyle.…”
Section: Figure 6 Graph Comparison Of Changing Cognition Between Mosc...supporting
confidence: 70%
“…Based on this, in line with the results of research by Brilliandita & Putrianti (2017), adolescents, in this case, students, who are dominant with a hedonic lifestyle, become unproductive, and in adolescent relationships, are more concerned with appearance or prestige. A hedonic lifestyle that must be supported by adequate financial capabilities will also become an even bigger problem if the achievement is carried out in all unhealthy ways, which will result in moral siltation for female students who adhere to a hedonic lifestyle.…”
Section: Figure 6 Graph Comparison Of Changing Cognition Between Mosc...supporting
confidence: 70%
“…Wells and Tigert (1971) define a hedonic lifestyle as using a person's finances and time. Meanwhile, according to Levan and Linda (2003), a hedonic lifestyle is a person's behavior, which can be seen from his activities, interests, and point of view, which tends to prioritize pleasure in his life. From this explanation, it can be concluded that a hedonic lifestyle is a person's lifestyle with pleasure or success that desired objects can fulfill.…”
Section: Pg 137mentioning
confidence: 99%
“…Sehingga saat lingkungan memberikan penilaian positif terhadap perilaku hedonistic lifestyle yang dimunculkan maka mahasiswa akan meningkatkan dan mengembangkan citra diri mahasiswa untuk mendapatkan image yang lebih baik lagi. Saat orang sudah terbiasa dengan gaya hidupnya yang mewah sulit untuk mengubah hidupnya menjadi sederhana (Brilliandita & Putrianti, 2015) Senada dengan penelitian Komariyah (2012) bahwa semakin tinggi citra diri maka gaya hidup fashion juga semakin tinggi. Komariyah (2012) menjelaskan bahwa citra diri yang tinggi merupakan salah satu gambaran kepribadian yang sehat.…”
Section: Hasil Dan Pembahasanunclassified
“…Hedonistic lifestyle ini akan menjadi ciri khas dari mahasiswa yang akan membentuk identitas yang berbeda dengan identitas pada masa remaja Penelitian ini penting untuk diteliti yang pertama karena belum pernah ada penelitian yang dapat membuktikan pengaruh antara citra diri terhadap kecenderungan hedonistic lifestyle. Penelitian sebelumnya yang telah diketahui oleh peneliti yaitu terkait penggabungan hedonistic lifestyle dengan kontrol diri yang dilakukan penelitian oleh Azizah & Indrawati (2015), konsep diri yang dilakukan penelitian oleh Brilliandita & Putrianti (2015), persepsi yang dilakukan penelitian oleh Nadzir (2015), religiusitas yang dilakukan penelitian oleh Saputri & Risana (2016), Shoping Addiction yang dilakukan penelitian oleh Prasetyo (2017), konformitas teman sebaya yang dilakukan penelitian oleh Sholikhah & Dhania (2017), keluarga yang dilakukan penelitian oleh Trimartati (2014), regulasi emosi yang dilakukan penelitian oleh Anjelita (2017), Konsumtif yang dilakukan penelitian oleh Anggraini & Santhoso (2017), harga diri yang dilakukan penelitian oleh Maisyaroh (2016), dan kepribadian yang dilakukan penelitian oleh Amalia (2017).…”
unclassified